2022
DOI: 10.1186/s12909-022-03257-2
|View full text |Cite|
|
Sign up to set email alerts
|

Shaping the right conditions in programmatic assessment: how quality of narrative information affects the quality of high-stakes decision-making

Abstract: Background Programmatic assessment is increasingly being implemented within competency-based health professions education. In this approach a multitude of low-stakes assessment activities are aggregated into a holistic high-stakes decision on the student’s performance. High-stakes decisions need to be of high quality. Part of this quality is whether an examiner perceives saturation of information when making a holistic decision. The purpose of this study was to explore the influence of narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…38 This model is a strong step toward our goal of identifying low-quality comments (and raters) for faculty development and programmatic improvement. 8,9,39 Additionally, trainees have identified that collecting EPA assessments from supervisors represents a significant burden 40 ; we owe it to trainees to provide them with valuable and useful feedback if we are adding to their already busy workload.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…38 This model is a strong step toward our goal of identifying low-quality comments (and raters) for faculty development and programmatic improvement. 8,9,39 Additionally, trainees have identified that collecting EPA assessments from supervisors represents a significant burden 40 ; we owe it to trainees to provide them with valuable and useful feedback if we are adding to their already busy workload.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 When narrative comments are of low quality, confidence in high-stakes decisions regarding trainee performance and progression declines. 8,9 Educators have developed tools to evaluate the quality of narrative assessment comments in medical education. 5 The System for Improving and Measuring Procedural Learning (SIMPL), 10 Narrative Evaluation Quality Instrument (NEQI), 11 Evaluation of Feedback Captured Tool, 12 and Quality of Assessment for Learning (QuAL) 13 tools are used to rate the quality of narrative comments with the goal of supporting and quantifying improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article [ 1 ], the authors informed us that due to an error in the proofing process, one reference was not correctly in the reference list and the entire reference list needs to be updated.…”
mentioning
confidence: 99%